The last kids on Earth : June's wild flight - Brallier, Max (Brallier, Max. Last kids on Earth., 2020)
While the kids plan their next move, an unexpected threat emerges and June gets separated from her friends, dragged miles away from Wakefield to a town overgrown with monstrous vines and never-before-seen creatures. Drawing on her post-apocalyptic survival and action skills--and with the help of some odd new companions--June attempts to make her way back home. But not before she uncovers critical information about the mysterious "Tower." Information that the future of our world may hinge upon ...